Investigate Strategic Ambidexterity: How Environmental Dynamism Affects Networking Capability in Small Businesses - Tyna Yunita (Publisher Cv. Inara, 2023)
This study intends to investigate strategic ambidexterity (STA) by examining how environmental dynamism (EN) affects networking capability (NE) in small businesses. In addition, the moderating influence of EN on the relationship between NE and STA is examined. The association between networking capability, environmental dynamism, and strategic ambidexterity was determined by analyzing the responses from a survey of 185 small business owners in the province of West Java. The research has employed survey questionnaires and smart PLS for data analysis. This study indicated that small business networking capability and environmental dynamism directly affected strategic ambidexterity. However, this study's outcomes reveal that environmental dynamism as a moderator in the relationship between networking capability and strategic ambidexterity is insignificant.